MARKET NAMES IN MEDAN: A NATURAL SEMANTIC METALANGUAGE STUDY - Latifah Yusri Nasution; Mulyadi Mulyadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This article aims to investigate market names in Medan. This study used natural semantic metalanguage theory. The type of this research is descriptive qualitative. In data collection, interviews and observations were conducted. The results showed that Medan people named their markets based on the markets’ location, time and environmental conditions. Market names in Medan contain denotative or connotative meaning. The difference in the market name’s meaning reflects thoughts underlying the word. The paraphrase of the market name’s meaning can provide an understanding of the use of market names in Medan.